Uptake of Cervical Cancer Screening and Its Determinants among Refugee Women in Uganda: Insights from the Uganda Refugee Population-based HIV Impact Assessment - Kikonyogo, Steven; Derrick, Bary Abila; Ezra, Anecho; Candia, Godwin Ivan; Barungi, Brenda Banana; Priscilla, Nambalirwa; Anthony, Kayiira (Journal of Cervical Cancer, 2025)
Cervical cancer is the fourth most common cancer in women globally, with 660,000 new cases and 350,000 deaths in 2022. The burden is disproportionately high in low- and middle-income countries (LMICs), particularly sub-Saharan Africa. Despite proven interventions like HPV vaccination and screening, uptake remains low. While cervical cancer screening has been studied in the general population, little is known about uptake among refugee women in Uganda, which hosts approximately 1.7 million refugees. This study examines cervical cancer screening uptake and associated factors among refugee women in Uganda. Methods We conducted a cross-sectional secondary analysis of the 2021 Uganda Refugee Population-based HIV Impact Assessment (RUPHIA) survey, focusing on women aged 21–49 in refugee settlements in the West Nile and South-Western regions, which host 90% of Uganda’s refugee population. The primary outcome was self-reported cervical cancer screening status. We used descriptive statistics and logistic regression to identify factors associated with screening uptake. Results Among 731 women, only 72 (9.8%) reported undergoing cervical cancer screening. The mean age of screened women was 37 years (±7), compared to 32 years (±8) for unscreened women. Screening uptake was significantly higher among women aged 31–39 years (AOR = 2.67, 95% CI: 1.32–5.52, p = 0.007), married women (AOR = 12.0, 95% CI: 1.76–163, p = 0.03), and those in polygamous relationships (AOR = 4.76, 95% CI: 1.96–11.1, p < 0.001) Conclusion Cervical cancer screening uptake among refugee women in Uganda is critically low. Integrating culturally sensitive screening programs into refugee health services and addressing socio-economic barriers could improve access and utilization.
Keywords: Cervical cancer screening; Refugee women; Screening uptake; Uganda